Breast Diffuse Large B-cell Lymphoma, Activated B-cell like Subtype: A Case Report - Sneha Samir Babaria; Jinalben Shaileshbhai Patel (Journal of Clinical and Diagnostic Research)
Primary Breast Lymphoma (PBL) is an uncommon form of Non Hodgkin Lymphoma (NHL) that arises within the breast tissue, representing less than 1-2% of all cases of NHL and under 0.5% of all breast cancers. Most PBL cases are of the B-cell type, accounting for up to 50% of all PBL. Diffuse Large B-cell Lymphoma (DLBCL) of the breast is a rare subtype of NHL, with a common age of presentation in females being 50-60 years. It typically presents as a painless breast mass without pathognomonic radiologic findings. Authors hereby, report a case of a 43-year-old female who complained only of heaviness in the right breast, followed by a discretely palpable lump upon examination. High-grade NHL was diagnosed via core needle biopsy and turned out to be DLBCL, Activated B-cell (ABC)-like subtype, as determined by Immunohistochemistry (IHC). This study emphasises that histopathological analysis of core needle biopsy with IHC is paramount for establishing the diagnosis and distinguishing it from other benign and malignant breast conditions. By sharing this case, authors aimed to contribute to the growing knowledge of this rare entity, which has steadily increased over the past four decades, to ensure timely and accurate diagnosis for the implementation of appropriate therapy.